Participation and Persistence of Adult Basic Education Students at a Rural College Campus on Manitoulin Island - Prechotko, Christopher; Kirby, Dale (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
Little research has been conducted to examine the participation and persistence of adult basic education students in northern and rural Canada. This explanatory sequential mixed-methods study was conducted with adult learners to address this research deficit. The study consisted of questionnaire and interview phases. Using thematic analysis, five themes were identified from the participant responses: (a) positive, supportive, personal touch; (b) situational hardships; (c) friendships and community; (d) campus Indigeneity; and (e) program resources. Situational hardships directly affected students’ program participation and persistence. A positive, supportive environment contributed to participation and persistence, while friends, community, and program resources influenced student persistence in the program. Participants identified campus Indigeneity and promotion of the program as areas for improvement.